Effect of Drug-Coated Balloon in Side Branch Protection for de novo Coronary Bifurcation Lesions: A Systematic Review and Meta-Analysis - Zheng, Yawei; Li, Jie; Wang, Lingzhun; Yu, Peng; Shi, Haibo; Wu, Lihua; Chen, Jiandong (Frontiers in Cardiovascular Medicine, 2021)
Background: At present, there are a variety of treatment strategies for percutaneous coronary intervention. The role of drug-coated balloon (DCB) in the treatment of side branch for de novo coronary bifurcated lesions (CBL) is unclear. Objective: To examine the effect of DCB in side branch protection for de novo CBL. Methods: Electronic databases, including Pubmed, Embase, the Web of science, Cochrance library, CNKI, CBM, WanFang Data and VIP were searched for studies that compared DCB with non-drug-coated balloon (NDCB) in side branch protection for de novo CBL from inception through July 7th, 2021. The primary outcome was target lesion revascularization (TLR). Secondary clinical outcomes included myocardial infarction (MI), cardiac death (CD). The angiographic outcomes included side branch late lumen loss (LLL), minimum lumen diameter (MLD), diameter stenosis (DS) and binary restenosis (BR). The target lesion failure (TLF) was also analyzed. Results: A total of 10 studies, including 5 randomized controlled trials and 5 non-randomized observational studies, with 934 patients were included. Meta-analysis results of angiographic outcomes suggested that DCB group had the less LLL, DS and BR and the higher MLD compared with NDCB group at follow-up (P < 0.05). Meta-analysis results of clinical outcomes suggested that the significant difference in the TLR, MI and CD between DCB group and NDCB group has not been found yet (P > 0.05). However, the MACE of DCB group was significantly less than that of NDCB group at 9-month follow-up [OR = 0.21, 95%CI (0.05, 0.84), P = 0.03] and 12-month follow-up [OR = 0.45, 95%CI (0.22, 0.90), P = 0.02]. In addition, there was no significant difference in TLF between DCB group and NDCB group (P > 0.05). Conclusions: DCB had great effect in side branch protection for de novo CBL at short and medium-term follow-up with no reduction in the procedural success rate. Systematic Review Registration:https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=267426, PROSPERO [Identifier: CRD42021267426].